Active and Reactive Power Control of a Doubly Fed Induction Generator - Zerzouri Nora; Labar Hocine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Wind turbine WT occupies gradually a large part in world energy market, Doubly fed induction generator DFIG is mostly used in WT, it allow highly flexible active and reactive power generation control. This paper presents dynamic modeling and simulation of a doubly fed induction generator based on grid-side and rotor-side converter control. The DFIG, grid-side converter, rotor-side converter, and its controllers are performed in MATLAB/Simulink software. Dynamic response in grid connected mode for variable speed wind operation is investigated. Simulation results on a 3 MW DFIG system are provided to demonstrate the effectiveness of the proposed control strategy during variations of active and reactive power, rotor speed, and converter dc link voltage.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6477